Isomorphism Conditions for Cayley Graphs of Rectangular Groups - Sayan Panma (2018)
© 2015, Malaysian Mathematical Sciences Society and Universiti Sains Malaysia. A rectangular band is defined as a direct product of a left zero semigroup and a right zero semigroup, and a rectangular group is defined as a direct product of a group and a rectangular band. In this paper, we give some equivalent conditions for Cayley graphs of a rectangular group to be isomorphic to each other.